Lecture-compréhension en français : le constat d'un besoin aux derniers cycles universitaires - Spoto Zabala, Daniela (2022)
During the last decade of the 20th century and the early years of the 21st century, the teaching of French as a foreign language has been greatly reduced in the formal and compulsory education system of Argentina. This situation caused adverse consequences (Spoto Zabala, 2021:15). Despite this situation, french is still present at the university level in Argentina as Reading-Comprehension Courses, FOS and FOU courses; and the existence of a high demand in recent university cycles has been noted. Therefore, to try to overcome this lack, an intensive course on Reading-Comprehension in French has been designed and implemented. Here are some results from the data collection and needs analysis.
Pendant la dernière décennie du XXe siècle et les premières années du XXIe, l'enseignement du français langue étrangère a été fortement réduit dans le système éducatif formel et obligatoire de l'Argentine provocant des conséquences néfastes (Spoto Zabala, 2021 :15). Malgré cette situation, le français reste toujours présent au niveau supérieur et universitaire en Argentine sous forme de cours de Lecture-compréhension, de FOS et de FOU ; et l'existence d'une forte demande aux derniers cycles universitaires a été constatée. Par conséquent, pour essayer de pallier ce manque un cours intensif portant sur la lecture-compréhension en français a été conçu et mis en marche. Voici quelques résultats issus de la collecte de données et de l'analyse des besoins.
Keywords: Reading-Comprehension; FOS; FOU; 2nd and 3rd University Cycles; Argentina; Lecture-compréhension; FOS; FOU; 2e et 3e cycles universitaires; Argentine^lfr